Aqueous Solutions of a Porous Host–Poly‐L‐lysine Complex with Information on Solids as Different Fluorescence by Guests. Issue 23 (13th October 2022) - Takahashi, Katsuya; Umezane, Sota; Ono, Toshikazu; Fukutomi, Satoshi; Ihara, Megumi; Hisaeda, Yoshio; Kawasaki, Riku; Ikeda, Atsushi
Abstract: N, N' ‐Dipyrid‐3‐yl‐1, 4, 5, 8‐naphthalenediimide linked to two tris(pentafluorophenyl)borane (1 ) exhibits strong fluorescence emission in the solid state by the formation of a charge‐transfer complex containing small aromatic guest molecules. Hydrophobic 1 was dissolved in water by mixing with poly‐L‐lysine (PLL) as a solubilizing agent. The 1 ‐PLL complex could include small aromatic guest molecules in water, significantly increasing the fluorescence. The fluorescence maxima of 1 in aqueous solution and solid state were different depending on the guest molecule. Therefore, compound 1 was prepared as aqueous solution with information of fluorescence on solids by complexation with PLL. Abstract : Compound 1 was dissolved in water by complexation with poly‐L‐lysine, and the complex exhibited fluorescence depending on the aromatic guest molecules in water and solid state.